My not so perfect life - Kinsella, Sophie (ill., 2017)
Katie Brenner has the perfect life: a flat in London, a glamorous job, and a super-cool Instagram feed. Ok, so the real truth is that she rents a tiny room with no space for a wardrobe, has a hideous commute to a lowly admin job and the life she shares on Instagram isn't really hers. But one day her not-so-perfect life comes crashing down when her mega-successful boss Demeter gives her the sack. Forced to move back home to Somerset, Katie has to restart from square one. But when fate gifts her the chance to take revenge on Demeter, should Katie get medieval on the woman who ruined her dreams?